Epigenetic Reprogramming by Somatic Cell Nuclear Transfer in Primates - Sparman, Michelle; Dighe, Vikas; Sritanaudomchai, Hathaitip; Ma, Hong; Ramsey, Cathy; Pedersen, Darlene; Clepper, Lisa; Nighot, Prashant; Wolf, Don; Hennebold, Jon; Mitalipov, Shoukhrat (Stem cells (Dayton, Ohio), 2009)
We recently demonstrated that somatic cells from adult primates could be reprogrammed into a pluripotent state by somatic cell nuclear transfer. However, the low efficiency with donor cells from one monkey necessitated the need for large oocyte numbers. Here, we demonstrate nearly threefold higher blastocyst development and embryonic stem (ES) cell derivation rates with different nuclear donor cells. Two ES cell lines were isolated using adult female rhesus macaque skin fibroblasts as nuclear donors and oocytes retrieved from one female, following a single controlled ovarian stimulation. In addition to routine pluripotency tests involving in vitro and in vivo differentiation into various somatic cell types, primate ES cells derived from reprogrammed somatic cells were also capable of contributing to cells expressing markers of germ cells. Moreover, imprinted gene expression, methylation, telomere length, and X‐inactivation analyses were consistent with accurate and extensive epigenetic reprogramming of somatic cells by oocyte‐specific factors. STEM CELLS 2009;27:1255–1264